Effects of Working Medium Gases on Emission Spectral and Temperature Characteristics of a Plasma Igniter - Gao Cheng Chen; Li Ming He; Bing Bing Zhao; Hua Lei Zhang; Zi Chen Zhao; Hao Zeng; Jian Ping Lei; Xiong Liu (Journal of Spectroscopy)
Ar, N2, O2, and N2-O2 mixture under different O2 components were separately used as the working medium gas of a plasma igniter to study the influence of working-medium-gas type and O2 concentration on emission spectral and temperature characteristics of a direct-current arc plasma igniter. The emission spectra of the plasma jet were also analyzed using the optical emission spectroscopy method, and the influence rule of working medium gas and O2 concentration on electron temperature and vibrational temperature of the plasma jet was calculated and analyzed. The experimental results show that the emission spectra of the plasma jet had significant differences when diverse working gases were used as the working medium of the igniter. With increasing O2 concentration in the working medium gas, the spectral line intensity of oxygen-containing particles in emission spectra of the plasma jet was significantly enhanced, and the spectral intensities of nitrogen-containing particles, NO molecular bands, the second positive system of N2C3∏u−B3∏g, and the first negative system of N2+B2∑u+−X2∑u+ were also enhanced obviously. Both electron and vibrational temperature of the plasma jet increased gradually with increasing O2 concentration in the working medium gas, and first increased and then decreased with increasing axial distance from the plasma jet.